STUDENTS' PERCEPTIONS OF THE IMPLEMENTATION OF LITERATION PROGRAM - Irawan, Tata Regita Sherfaty; Vonti, Lungguh Halira; Herawati, Atti (Journal of English Teaching and Linguistics Studies (JET Li), 2024)
The purpose of reading is to get information or an understanding of what the reader wants to convey through the text. However, interest in reading is still a big problem in Indonesia. This study aims to look at students' positive perceptions of the implementing literation program. This study employed a qualitative method and used questionnaires and interviews as research instruments. There were 33 students as research respondents taken from the pioneer class at private senior high school. The results of this study indicate that the PESAT literation program plays an important role in increasing students' interest in reading, improving their reading skills, assisting them in acquiring new insights through reading books as well as developing their reading, writing, and speaking skills.